Laboratory Evaluation of Microencapsulated Formulations of Chlorpyrifos-Methyl Against Black Fly Larvae (Diptera: Simuliidae) and Selected Nontarget Invertebrates - Rodrigues, C. S.; D. P. Molloy; Kaushik, N. K. (The Canadian Entomologist, 1983)
Laboratory tests were conducted under simulated stream conditions to determine the efficacies of microencapsulated formulations of chlorpyrifos-methyl (Reldan® 10–10) against Simulium and Prosimulium late-instar larvae. In tests with eight formulations, no correlation was evident between efficacy and formulation stability (i.e., cross-linking ratio). The most effective formulations were 34-75-50A, 119-75-6A, and 119-75-6C. The LC50 and LC90 values of 34–75–50A against S. vittatum were 5.5 μg/L and 24 μg/L/10 min. respectively. The formulations 119-75-6A and 119-75-6C were statistically not different from 34-75-50A. Prosimulium magnum was less susceptible (LC50 = 36μg/L, LC90 = 205 μg/L). Susceptibility among S. vittatum larvae varied inversely with size. Treatment with formulation 34-75-50A at 237 μg/L/10 min (the observed LC100 for S. vittatum) severely affected nymphs of the mayfly Baetis sp. and the stonefly Taeniopteryx burksi, but had a minimal effect on most other detritivores, filter-feeding caddisflies (Hydropsyche betteni and Brachycentrus sp.), and predators. Mortality increased significantly in some of these latter species, however, when exposed to 492 μg/L/10 min (the observed LC100 for P. magnum). Tests indicated that there was some leakage of active ingredient from the microcapsules into the water. Although the microencapsulated formulations of chlorpyrifos-methyl were designed to have selective toxicity to black fly larvae, our laboratory tests indicated that they were not as safe towards nonfilter feeders as had been expected.
Keywords: biology